Pembelajaran Musik Ansambel di Kelas VII MTSN 03 Kota Padang - Yoga Saputra; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2022)
The purpose of this lesson is for students to understand concepts and types and be able to play ensemble music. This type of research is qualitative descriptive research. The types of data used in this research are primary and secondary data. Data collection techniques were carried out through observation, interviews, documentation, and literature study. The stages of data analysis are data classification, data purification, data analysis, data description, and data inference. Based on the results of this study, it was revealed that in meetings I, II, III, and IV, the process of implementing learning, on average, students already understood the basic concepts of ensemble music. Still, some students did not understand the types of ensemble music, and examples of ensemble music could not be classified. Students already know how to play the recorder well, although a few students have not mastered how to play the recorder with ascending and descending techniques. However, overall, the ensemble music learning in class VII MTsN 03 Padang City is good.